Pengaruh Penerapan Blended learning terhadap Hasil Belajar Siswa pada Mata Pelajaran Dasar Listrik Elektronika - Rifki Ilham; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The use of (conventional) lecture methods in the process of teaching activities can take place well if students have the ability to listen and hear well.This can have an impact on the lack of maximum student activity in the teaching and learning process because of one-way communication.This encourages research on the application of blended learning methods in the basic subjects of electronic electricity at SMK Muhammadiyah Padang.The study used descriptive methods with a quantitative approach and the subject used was class X TITL.Data collection is done by documentation method and test method with the number of questions as many as 25 questions.Data analysis is done with descriptive analysis methods with the help of Microsoft Excel applications so that minimal values, maximum values, mean, median, mode, and frequency distribution are obtained.The results of this study showed that the use of blended learning methods was ineffective because the value of students who did not reach KKM ≥ 75.Test results showed that 50% of students obtained low grades and 7% of students obtained very high grades that almost reached KKM ≥ 75.Thus the blended learning method still cannot be applied to the basic subjects of electronic electricity.